2014
DOI: 10.15288/jsad.2014.75.249
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Administered Alcohol on Intimate Partner Interactions in a Conflict Resolution Paradigm

Abstract: ABSTRACT. Objective: Although couples' alcohol use has been associated with intimate partner aggression and poorer marital functioning, few studies have examined the proximal effects of alcohol on couple interactions. The current experimental study examined the effects of alcohol, administered independently to male and female intimate partners, on positive and negative interaction behaviors within a naturalistic confl ict resolution paradigm. Method: Married and cohabiting couples (n = 152) were recruited from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 54 publications
(62 reference statements)
2
39
1
Order By: Relevance
“…The current study used alcohol-administration methods combined with a couples’ conflict paradigm in order to explore the link between relationship quality and acute alcohol response among interacting couples. Previous analyses suggested positive effects of alcohol on couples’ behaviors (Testa et al, 2014); however, consistent with hypotheses, the current analyses revealed that these effects were largely specific to individuals unhappy in their intimate partnerships.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The current study used alcohol-administration methods combined with a couples’ conflict paradigm in order to explore the link between relationship quality and acute alcohol response among interacting couples. Previous analyses suggested positive effects of alcohol on couples’ behaviors (Testa et al, 2014); however, consistent with hypotheses, the current analyses revealed that these effects were largely specific to individuals unhappy in their intimate partnerships.…”
Section: Discussionsupporting
confidence: 78%
“…Interrater agreement was acceptable (67%, average Cohen’s Kappa=.50). Consistent with our own prior work (e.g., Fairbairn & Sayette, 2013; Sayette et al, 2012; Testa et al, 2014), as well as other work in this tradition (see Fairbairn et al, 2015 for a review), we did not explore each negative and positive behavioral code separately, but instead summed across all codes within each category to create composite negative and positive behavioral frequency indexes. Here, as elsewhere (e.g., Cranford, Tennen, & Zucker, 2015), we found that several of the negative behaviors (e.g., psychological abuse, withdrawal) did not manifest with sufficient frequency to permit independent examination of these behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…Two studies appearing in the same article made us of a negative evaluative feedback paradigm (Rohsenow & Bachorowski, 1984). The remaining studies used a teacher/learner method (Gustafson, 1991), the conflict resolution paradigm in which romantic partners discuss an issue upon which they disagree (Testa, Crane, Quigley, Levitt, & Leonard, 2014), a first-person video vignette in which participants were asked to provide likely behavioral responses to provocation (Ogle & Miller, 2004), and the Articulated Thoughts in Simulated Situations paradigm (ATSS; Davison, Robins, & Johnson, 1983) in which participants verbally respond to ambiguous audio interactions between a simulated romantic partner and various other individuals (Eckhardt & Crane, 2008). …”
Section: Methodsmentioning
confidence: 99%
“…To be eligible, both partners drank four or more drinks on an occasion at least once per month; neither partner reported medical contraindications to alcohol consumption or met criteria for alcohol dependence; and neither partner reported extremely severe partner violence (e.g., use of weapon, injury requiring medical attention). Additional details regarding recruitment and screening are provided in Testa and Derrick (2014) and Testa et al (2014).…”
Section: Methodsmentioning
confidence: 99%